Becket - Wallis, Hal B., 1899-1986.; Anhalt, Edward, 1914-2000.; Glenville, Peter, 1913-1996.; O'Toole, Peter, 1932-; Burton, Richard, 1925-1984.; Gielgud, John, 1904-2000.; Wolfit, Donald, 1902-1968.; Hunt, Martita; Brown, Pamela, 1917-1975.; Anouilh, Jean, 1910-1987.; Merrick, David, 1911-2000.; CPI (Firm); et al. ([Orland Park, Ill.] : MPI Home Video, 2007)
Henry II surprises England by naming his fellow rogue and trusted confidant Thomas Becket as Chancellor. But when Henry next appoints him Archbishop of Canterbury, Becket shocks the world by openly defying the King with his newfound faith and compassion. Will a desperate ruler now destroy a beloved friend to save his splintering kingdom?
Title from container.
Based on the Broadway play "Becket" by Jean Anouilh ; produced upon the stage by David Merrick.
Originally released as a motion picture in 1964.
"Restored by the Academy Film Archive Restoration Funding provided by The Film Foundation."
Special features: Commentary with Peter O'Toole; interviews with editor Anne V. Coates and composer Laurence Rosenthal; archival interviews with Richard Burton; theatrical trailer; still gallery; TV spot.
Peter O'Toole, Richard Burton, John Gielgud, Donald Wolfit, Martita Hunt, Pamela Brown.
Keywords: Henry -- II, -- King of England, -- 1133-1189 -- Drama; Thomas, -- B̉ecket, Saint, -- 1118?-1170 -- Drama; Privy councils -- England -- Drama; Friendship -- England -- Drama; Great Britain -- Kings and rulers -- Drama; England -- Social life and customs -- 1066-1485 -- Drama; England -- Drama; Feature films; Historical films